2009
DOI: 10.1016/j.genm.2009.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Nociceptive and anxiety-like behavior in reproductively competent and reproductively senescent middle-aged rats

Abstract: Background-Changes in levels of estradiol and progesterone that occur with the transition to reproductive senescence may influence nociception or affect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 72 publications
2
20
0
1
Order By: Relevance
“…2E and 3). In line with the presented data, reproductively senescence female rats (12-14 months old) have increased anxiety compared to reproductively competent rats as assessed in the elevated plus-maze, elevated zero maze, and Vogel punished drinking task [22]. In addition, rodents subjected to a chemical-induced perimenopause phase also display increased anxiety [15].…”
Section: Discussionsupporting
confidence: 86%
“…2E and 3). In line with the presented data, reproductively senescence female rats (12-14 months old) have increased anxiety compared to reproductively competent rats as assessed in the elevated plus-maze, elevated zero maze, and Vogel punished drinking task [22]. In addition, rodents subjected to a chemical-induced perimenopause phase also display increased anxiety [15].…”
Section: Discussionsupporting
confidence: 86%
“…periestropause) presented more anxiety-like behavior (Walf et al, 2009b). The 'periestropause' is characterized by irregular cycles associated with 65% of successful pregnancies and a fecundity average of less than 10 pups per litter (Walf et al 2009b). Unfortunately, in the present study the index fecundity was not evaluated; however, 40% of 7-8-month-old females presented longer cycles, supporting the idea that these animals were closer to estropause.…”
Section: Discussionsupporting
confidence: 46%
“…Supporting this, it has been reported that middle-aged female rats that were transitioning to reproductive senescence (i.e. periestropause) presented more anxiety-like behavior (Walf et al, 2009b). The 'periestropause' is characterized by irregular cycles associated with 65% of successful pregnancies and a fecundity average of less than 10 pups per litter (Walf et al 2009b).…”
Section: Discussionmentioning
confidence: 85%
“…Hypothalamic nuclei and their inputs and outputs from other limbic brain regions [e.g., bed nucleus of the stria terminalis (BnST) and amygdala] are involved in the regulation of reproduction, mood, and memory, in part through actions of gonadal steroid hormones on their receptors in the brain (Arimoto et al, 2013, Hogervorst et al, 2005, Rosario et al, 2010, Smith et al, 1992, Walf et al, 2009). The principal estrogen, estradiol (E2), has been extensively studied for age-related changes in neurobiological actions in females, but to a much lesser extent in males (Foster, 2012, Harburger et al, 2009, Raber, 2008, Russell et al, 2012, Walf et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Hypothalamic nuclei and their inputs and outputs from other limbic brain regions [e.g., bed nucleus of the stria terminalis (BnST) and amygdala] are involved in the regulation of reproduction, mood, and memory, in part through actions of gonadal steroid hormones on their receptors in the brain (Arimoto et al, 2013, Hogervorst et al, 2005, Rosario et al, 2010, Smith et al, 1992, Walf et al, 2009). The principal estrogen, estradiol (E2), has been extensively studied for age-related changes in neurobiological actions in females, but to a much lesser extent in males (Foster, 2012, Harburger et al, 2009, Raber, 2008, Russell et al, 2012, Walf et al, 2009). Furthermore, the literature in male rodents and humans on whether and how serum E2 changes with aging is inconsistent; various groups have reported increases (Fujita et al, 1990, Herath et al, 2001, Jasuja et al, 2013, Lakshman et al, 2010, Luine et al, 2007), decreases (Khosla et al, 2001, Leifke et al, 2000, van den Beld et al, 2000, Wu and Gore, 2009, Yeap et al, 2012), or no change (Goya et al, 1990, Gruenewald et al, 1994, Yeap et al, 2014) with advanced age.…”
Section: Introductionmentioning
confidence: 99%